The usefulness of monocyte fluorescence as a biomarker of Tuberculosis infection at Chris Hani Baragwanath Academic Hospital - Moosa, Aamina Yunus (University of the Witwatersrand, Johannesburg, 2023)
Introduction: South Africa has the 5th highest burden of Tuberculosis (TB) as well as coinfection with Human immunodeficiency virus (HIV) worldwide. Routine laboratory methods have varying sensitivity and specificity. The Xpert MTB/RIF (GXPU) (Cepheid, Sunnyvale, CA), has lower sensitivity in sputum smear negative cases and poor quality sputum samples. A robust, non-sputum based, inexpensive biomarker of TB would be of value in such cases. Monocytes are the major leucocyte involved in the immune response to TB. The Sysmex haematology analysers (Sysmex, Kobe, Japan) measure monocyte activation via monocyte fluorescence (MO-Y). This study aimed to evaluate the MO-Y and other Sysmex extended differential parameters (EDPs) as biomarkers of TB infection in the local setting. Methods: The MO-Y and EDPs were retrieved from the analyser for 121 adult cases (56 with TB, 65 controls). Further information was obtained from the laboratory information system, including patient demographics and other laboratory results; TB culture, SARS-CoV-2 results, C-reactive protein level, HIV status, bone marrow biopsies and the cycle threshold (CT) values on positive GXPU analysis. The MO-Y, EDPs and full blood count (FBC) values were compared among patients with and without TB (HIV positive and negative). Statistical significance was assessed (P-value of <0.05). Results: The MO-Y did not show utility in identifying patients with TB. A sub-population of patients living with HIV (PLWH) with a CD4 <100 cells/ul showed significantly higher MO-Y levels, due to other opportunistic infections affecting monocytes. Neutrophil surface fluorescence (a marker of neutrophil activation), was significantly higher in PLWH and with concomitant TB infection, possibly due to immune activation, worse illness, or increased bacterial infection. Among the PLWH, those with TB had significantly lower CD4 counts, absolute lymphocyte counts and mean cell volume (MCV) values. The MCV (cut-off value 87 fL) showed the strongest diagnostic utility for discriminating PLWH with and without TB (AUC 0.79). Conclusion: The MO-Y is not a useful biomarker of TB, but is significantly elevated in PLWH with low CD4 counts. The MCV showed adequate discriminatory power for differentiating patients with and without TB, at a cut-off level of 87fL.
A research report (in the format of a “submissible” paper) submitted in partial fulfilment of the requirements for degree of Master of Medicine in the branch of Haematology, to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2023
Keywords: Tuberculosis (TB); Human immunodeficiency virus (HIV); Monocytes; Leucocyte; Sysmex haematology analysers (Sysmex; Kobe; Japan); SARS-CoV-2; Patients living with HIV (PLWH); UCTD; SDG-3: Good health and well-being